Study on quenching effect of nitrite ions on zinc oxide modified by polyvinylpyrrolidone - Ing, Hua Tang (2015)
Zinc oxide (ZnO) is appeared to be an attractive material for application for multidisciplinary fields, owing to its unique physical and chemical properties. In this study, ZnO was synthesized using the co-precipitation method, where the zinc acetate was used as the precursor. The ZnO was further modified by adding different amounts of polyvinylpyrrolidone (PVP) via simple physical mixing method to obtain ZnO-PVP composites. The ZnO and the ZnO-PVP composites were characterized using Fourier transform infrared (FTIR), diffuse reflectance ultraviolet-visible (DR UV-Vis), and fluorescence spectroscopy. The FTIR spectra detected the presence of ZnO group and the functional groups from the PVP. The PVP peaks become more apparent with the increase of the PVP amount. From the DR UV-Vis spectra, no significant change was observed after modification with the PVP, and all composites showed similar broad absorption band to that of the ZnO. The fluorescence spectra showed that the addition of PVP decreased the emission intensity and red shifted the peak wavelength, indicating certain interactions between the ZnO and the added PVP. Quenching study was investigated in the presence of nitrite ions (NO2 -) with various concentrations (2-10 µM). A linear Stern-Volmer plot was observed and the highest quenching constant rate (KSV) was obtained on the ZnO-PVP sample with PVP content of 0.1 wt%. This study demonstrated that the addition of the PVP on the ZnO improved the interaction between the ZnO and the NO2 -, which will be one of the important factors for sensing and catalytic applications for detection and conversion of NO2.